2018
DOI: 10.1111/1365-2745.13098
|View full text |Cite
|
Sign up to set email alerts
|

Ageing in an herbaceous plant: Increases in mortality and decreases in physiology and seed mass

Abstract: 1. Little is known about plant age-dependent trait expression and how environmental conditions might affect ageing in the wild. This study evaluates age variation in multiple traits of a short-lived perennial herb using a manipulative field experimental design.2. Two different-aged cohorts were followed in a field plot for over a year to evaluate trait expression in response to a competition treatment and seasonal stress. Traits measured included size, mortality, reproduction, and physiology, including photosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Declines were found in three species, but one of these species Pinus sylvestris (Mencuccini, Oñate, Peñuelas, Rico, & Munné-Bosch, 2014) showed declines in some physiological traits but negligible change in other traits. In the other two species, Cistus clusii (Munné-Bosch & Lalueza, 2007) and Plantago lanceolata (Quarles & Roach, 2019), cross-sectional studies showed that older individuals had lower physiological performance, but for several traits these agedependent declines were only manifest during stressful conditions.…”
Section: Age Trajectories Among Species and Among Traitsmentioning
confidence: 99%
“…Declines were found in three species, but one of these species Pinus sylvestris (Mencuccini, Oñate, Peñuelas, Rico, & Munné-Bosch, 2014) showed declines in some physiological traits but negligible change in other traits. In the other two species, Cistus clusii (Munné-Bosch & Lalueza, 2007) and Plantago lanceolata (Quarles & Roach, 2019), cross-sectional studies showed that older individuals had lower physiological performance, but for several traits these agedependent declines were only manifest during stressful conditions.…”
Section: Age Trajectories Among Species and Among Traitsmentioning
confidence: 99%
“…, Dahlgren et al. , Quarles and Roach ). It has been suggested that some plants may even show “negative senescence,” an increasing survival probability after the onset of reproduction (Vaupel et al.…”
Section: Introductionmentioning
confidence: 97%
“…However, the long-term studies that do exist show conflicting results regarding how age affects fecundity and survival. Several studies indicate no or negligible senescence in plants (Harper and White 1974, Rose et al 1998, Hutchings 2010, Dahlgren et al 2016c, but there are also recent studies that have found evidence of demographic senescence (Pico and Retana 2008, Roach et al 2009, Dahlgren et al 2016b, Quarles and Roach 2018. It has been suggested that some plants may even show "negative senescence," an increasing survival probability after the onset of reproduction (Vaupel et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Plant size was estimated as the natural logarithm of the product of the maximum leaf length and the sum of all leaves (Noe & Blom, 1982; van Groenendael & Slim, 1988; cf. Quarles & Roach, 2019). We defined growth as the differences in above‐ground size of each individual between annual censuses.…”
Section: Methodsmentioning
confidence: 99%
“…Yet other studies have reported the risk of death to be constant as plants age (Harper, 1967; Lauenroth & Adler, 2008; Law et al., 1977). Variation in plant demographic senescence has also been found not only for vital rates but also for physiological traits where some studies have reported no evidence for physiological declines with age (Lanner & Connor, 2001; Morales et al., 2013; Wang et al., 2020), but others have detected lower physiological performance in older individuals (Quarles & Roach, 2019).…”
Section: Introductionmentioning
confidence: 99%